The impact of jurisprudential rules in the Omani Civil Law and the Omani Judiciary = أثر القواعد الفقهية في القانون المدني العماني والقضاء العماني - Issa, Al Saidi Majid Mubarak; Omar, Muhammad Naim; Abdullah, Mohamad Asmadi (OCERINT International Organization Center of Academic Research, 2023)
The study aimed to discuss: the authority of the jurisprudential rules, and the extent of the influence of the jurisprudential rules in the Omani civil law, and in the Omani judiciary. The study adopted two approaches: the inductive approach and the descriptive analytical approach. The study concluded many results, perhaps in the forefront: the jurists agreed on the authority of the jurisprudential rules based on legal texts in several rules, while the jurists differed in invoking the jurisprudential rules in general. The Omani legislator attributed understanding, interpretation, interpretation and significance of the text to the rules and principles of Islamic jurisprudence, and this is evident in the Personal Status Law and the Civil Transactions Law. The adoption of jurisprudential rules with their words, branches, concept and meaning was; clearly visible in the Omani legislation. The rulings and principles of the Supreme Court took into account the purposes of Sharia in general, and the rules of jurisprudence in particular.